High-strength carbon fiber plate and processing technology thereof
By modifying the slurry of components such as epoxy resin, polyimide prepolymer, bismaleimide monomer and acid chloride modified carbon nanotubes using coupling agent, the interface bonding force between carbon fiber and resin matrix is optimized, and the strength-related problems of carbon fiber boards are solved, and high strength and good thermal stability are achieved.
Patent Information
- Application Number
- CN202510015338.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
During the process of composite with the resin matrix, there is a problem of poor interface bonding, resulting in internal stress and microcracks, weakening the overall strength of the carbon fiber board.
The slurry of components such as epoxy resin, polyimide prepolymer, bismaleimide monomer and acid chloride modified carbon nanotubes are used to modify the slurry of components such as epoxy resin, polyimide prepolymer, bismaleimide monomer and acid chloride modified carbon nanotubes. Through chemical bonding and cross-linking reactions, the interface bonding between carbon fiber and resin matrix is optimized, and the mechanical properties and thermal stability of the material are improved.
It significantly improves the strength and thermal stability of carbon fiber boards, can maintain good working performance for a long time in complex environments, and meets the needs of high strength and high thermal stability.
Smart Images

Figure BDA0005229738670000101 
Figure BDA0005229738670000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon fiber composite materials, and in particular to a high-strength carbon fiber plate and a processing technology thereof. Background Art
[0002] Carbon fiber has a high strength-to-weight ratio, and its tensile strength can reach several thousand megapascals, far exceeding traditional metal materials such as steel and aluminum, while its density is only about a quarter of that of steel. In the field of aerospace, the use of carbon fiber materials in aircraft can significantly reduce the weight of the structure, thereby reducing fuel consumption, increasing payload, and opening up new paths for space exploration and long-distance flight. Carbon fiber has excellent corrosion resistance and can serve for a long time in harsh chemical environments such as acid, alkali, humidity, and even the ocean. In application scenarios such as deep-sea exploration equipment in marine engineering and offshore wind power facilities, it can effectively resist seawater erosion, reduce maintenance costs, and extend the service life of equipment. Carbon fiber has excellent high-temperature resistance and can withstand temperatures of up to thousands of degrees Celsius. In high-temperature working conditions such as hot end components of aircraft engines and linings of high-temperature industrial furnaces, it maintains the stability and mechanical properties of the material to ensure the safe and efficient operation of key systems.
[0003] However, when carbon fiber is converted into the application form of carbon fiber board, many strength-related problems are exposed. Although the carbon fiber raw yarn itself has considerable strength, there may be problems with poor interface bonding during the composite process with the resin matrix. Some resins have large curing shrinkage rates, which will produce internal stress with the carbon fiber after curing, causing micro cracks at the interface. These cracks become stress concentration points, seriously weakening the overall strength of the carbon fiber board, so there is room for improvement. Summary of the invention
[0004] In order to improve the strength of a carbon fiber plate, the present application provides a high-strength carbon fiber plate and a processing technology thereof.
[0005] The present application provides a high-strength carbon fiber plate and its processing technology using the following technical solutions: In the first aspect, the present application provides a high-strength carbon fiber plate, which adopts the following technical solution: A high-strength carbon fiber plate, the raw materials for preparation include carbon fiber cloth and slurry, the slurry includes the following components by weight: 30-40 parts of coupling agent modified epoxy resin Polyimide prepolymer 20-30 parts 15-25 parts of bismaleimide monomer 3-5 parts of acyl chloride modified carbon nanotubes 8-12 parts of curing agent 5-10 parts of diluent 1-2 servings of antioxidants 1-2 parts of ultraviolet absorber.
[0006] The coupling agent-modified epoxy resin can form a chemical bond with the carbon fiber cloth at the molecular level by introducing the active groups of the coupling agent, tightly connecting the two. At the same time, it uses its own excellent film-forming properties and bonding properties to build a solid and continuous matrix structure for the board, effectively maintaining the overall mechanical integrity, ensuring that all parts work together to bear the load when stressed, thereby improving the strength of the board; polyimide prepolymer has outstanding heat resistance. Under high temperature conditions, various functional groups in its molecules, such as anhydride groups and amino groups, will spontaneously undergo cross-linking reactions. The strengthening process of this cross-linked structure can significantly improve the thermal stability of the material, effectively resist softening and deformation caused by high temperature, and ensure the structural reliability and durability of the board in a high temperature environment. Performance stability, thereby improving the strength of the board; the bismaleimide monomer contains two highly active maleimide functional groups, which can react chemically with other resin components during the polymerization reaction, greatly increasing the cross-linking density of the resin system, and then optimizing the internal network structure of the material, so that the strength and modulus of the board are significantly improved to meet the needs of high-strength application scenarios; the acyl chloride-modified carbon nanotubes, the acyl chloride groups on their surfaces have good chemical reactivity after modification, and can form a stable connection with the active groups in the resin in the system through covalent bonds, optimizing the interface bonding state between different components, so that the load can be efficiently transferred between the components, and improving the overall mechanical properties and strength from a microscopic level.
[0007] Preferably, the raw materials for preparing the coupling agent modified epoxy resin include bisphenol A epoxy resin, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
[0008] Bisphenol A epoxy resin has good mechanical properties and provides basic strength support for the board. The epoxy groups in its molecules can participate in the cross-linking reaction to build a stable resin network structure. The amino group of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane can form chemical bonds with the oxygen-containing functional groups on the surface of carbon fiber. After hydrolysis, the siloxane group can be closely connected with the epoxy resin, and the interfacial bonding force between the carbon fiber and the resin matrix is strengthened by bridging, so that the external force can be more efficiently transmitted from the carbon fiber to the resin matrix, and the load is synergistically carried, thereby improving the overall strength. The mercapto group in 3-mercaptopropyltriethoxysilane can participate in the curing reaction of epoxy resin, optimize the cross-linking network, and enhance the cohesion of the resin matrix. At the same time, the silane part improves the compatibility of epoxy resin with other components and reduces internal stress concentration. In a high temperature environment, the coupling agent-modified epoxy resin system can effectively inhibit the thermal motion of the molecular chain and hinder the thermal degradation process by virtue of its tight and stable chemical bonding and optimized cross-linking structure, thereby significantly improving the thermal stability of the material and ensuring the reliable performance of the high-strength carbon fiber board under severe thermal conditions.
[0009] Preferably, the coupling agent modified epoxy resin is prepared by the following steps: N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane are mixed and dispersed in ethanol, and stirred to obtain a coupling agent solution; the coupling agent solution is added to bisphenol A type epoxy resin, the temperature is raised and stirred to react, and the solvent is removed by rotary evaporation to obtain a coupling agent modified epoxy resin.
[0010] The carbon fiber plate prepared according to the above steps has high strength and good thermal stability, and can maintain good working performance for a long time under complex environmental conditions.
[0011] Preferably, the raw materials for preparing the polyimide prepolymer include a composite diamine monomer and 3,3',4,4'-benzophenone tetracarboxylic dianhydride.
[0012] The active amino group contained in the composite diamine monomer can rapidly undergo a nucleophilic addition reaction with the anhydride group in the 3,3',4,4'-dibenzophenone tetraacid dianhydride molecule at the initial stage of the polymerization reaction. As the reaction proceeds, a regular and long-chain polyimide molecular structure is gradually formed. This long-chain structure is intertwined and entangled with each other, greatly improving the intrinsic strength of the material, so that when the plate is subjected to external force, it can rely on the stable structure formed by the polyimide to effectively disperse the stress and avoid local concentrated fracture; the rigid benzene ring structure rich in the polyimide molecular chain and the strong hydrogen bonding formed within the molecule give the material excellent thermal stability. Under high temperature environment, the rigid benzene ring can limit the free rotation of the molecular chain, and the strong hydrogen bonding prevents the relative slip between the molecular chains. The synergistic effect of the two can effectively inhibit the thermal deformation of the material, so that the high-strength carbon fiber plate can maintain a stable structure and performance even under severe thermal conditions, thereby improving the thermal stability of the carbon fiber plate.
[0013] Preferably, the composite diamine monomer includes 4,4'-diaminodiphenyl ether and 1,3-bis(4-aminophenoxy)benzene.
[0014] 4,4'-diaminodiphenyl ether has a symmetrical and regular molecular structure. Its amino group can efficiently react with 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride to build a stable initial molecular chain structure, giving the material initial strength; the phenoxy structure of 1,3-bis(4-aminophenoxy)benzene breaks the tight stacking of conventional molecular chains and gives the molecular chain flexibility. When subjected to force, the two work together, and the rigid chain segment dominated by 4,4'-diaminodiphenyl ether serves as the core bearing structure to strongly support external forces. 1,3-bis(4-aminophenoxy)benzene The flexible phenoxy group of 4,4'-diaminodiphenyl ether is used for buffering, flexibly adjusting the relative position between molecular chains, evenly dispersing stress, reducing the risk of material fracture, and synergistically improving strength; in a high temperature environment, the rigid benzene ring of 4,4'-diaminodiphenyl ether and the rigid part of 1,3-bis(4-aminophenoxy)benzene jointly regulate the thermal motion of the molecular chain, and the flexible phenoxy group relieves the internal stress caused by thermal expansion and contraction. The strong hydrogen bonds formed within and between the two molecules further strengthen the molecular connection network and stabilize the material structure, thereby improving the thermal stability of the carbon fiber board.
[0015] Preferably, the molar ratio of the 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-benzophenone tetracarboxylic dianhydride is (0.6-0.7):(0.3-0.4):1.
[0016] The polyimide prepolymer prepared according to the above mass ratio has a good molecular chain structure and can effectively improve the strength and thermal stability of the carbon fiber board.
[0017] Preferably, the bismaleimide monomer includes 4,4'-bismaleimidodiphenylmethane.
[0018] The rigid diphenylmethane structure in 4,4'-bismaleimide diphenylmethane is its core support, which gives the molecular chain a high degree of rigidity and regularity. During the polymerization process, the bismaleimide functional groups at both ends can quickly undergo cross-linking reactions with other resin components in the system to construct a dense and high-strength three-dimensional network structure, effectively improving the strength of the material; in a high-temperature environment, the rigid diphenylmethane and the stable network formed by cross-linking can limit the thermal motion of the molecular chain, inhibit the slip and breakage of the molecular chain, so that the material can still maintain structural integrity under thermal shock, and improve the thermal stability of the carbon fiber board; this highly cross-linked structure also has excellent chemical stability, can resist the erosion of complex external chemical environments, and comprehensively improve the performance of high-strength carbon fiber boards, meeting the requirements for high strength and high thermal stability of materials in demanding fields such as aerospace and high-end equipment manufacturing.
[0019] Preferably, the raw materials for preparing the acyl chloride-modified carbon nanotubes include oxidized carbon nanotubes and thionyl chloride.
[0020] The surface of oxidized carbon nanotubes is rich in oxygen-containing functional groups. As a strong chlorinating agent, thionyl chloride can react chemically with these oxygen-containing functional groups and successfully introduce acyl chloride groups into the surface of carbon nanotubes. When compounded with the resin system later, the acyl chloride groups can react rapidly with active groups in epoxy resins, polyimide prepolymers, etc., such as hydroxyl groups and amino groups, and are tightly connected through chemical bonds, thereby optimizing the interfacial bonding between the two, so that stress can be efficiently transmitted under the action of external forces, greatly enhancing the overall strength of the material; carbon nanotubes themselves have high strength and high modulus, and can be evenly dispersed in the resin matrix after being modified with acyl chlorides, further enhancing the carrying capacity; the excellent thermal conductivity of carbon nanotubes can quickly dissipate heat and avoid local overheating. At the same time, the stable structure formed by its close combination with the resin can effectively inhibit the thermal motion of molecular chains in high temperature environments, synergistically resist thermal degradation, and improve the thermal stability of carbon fiber boards.
[0021] Preferably, the mass ratio of the oxidized carbon nanotubes to thionyl chloride is 1:(0.6-0.8).
[0022] The acyl chloride-modified carbon nanotubes prepared according to the above mass ratio have good compatibility and reactivity, and can effectively improve the strength and thermal stability of the carbon fiber board.
[0023] In a second aspect, the present application provides a processing technology for a high-strength carbon fiber plate, which adopts the following technical solution: A processing technology for a high-strength carbon fiber plate comprises the following steps: The carbon fiber cloth is impregnated into the slurry, and pressure is applied during the impregnation process to obtain a prepreg; the prepreg is heated and dried to obtain a preliminary cured prepreg; the preliminary cured prepreg is cut and placed in a mold for hot pressing, and after cooling, it is demolded to obtain a high-strength carbon fiber board.
[0024] The carbon fiber plate prepared according to the above steps has high strength and good thermal stability, and can maintain good working performance for a long time in complex and harsh environments.
[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Coupling agent modified epoxy resin can form chemical bonds with carbon fiber cloth at the molecular level by introducing active groups of coupling agents, tightly connecting the two. At the same time, it uses its excellent film-forming properties and bonding properties to build a solid and continuous matrix structure for the board, effectively maintaining the overall mechanical integrity, ensuring that all parts work together to bear the load when stressed, thereby improving the strength of the board; polyimide prepolymer has outstanding heat resistance. Under high temperature conditions, various functional groups in its molecules, such as anhydride groups and amino groups, will spontaneously undergo cross-linking reactions. The strengthening process of this cross-linking structure can significantly improve the thermal stability of the material, effectively resist softening and deformation caused by high temperature, and ensure the structural reliability of the board in a high temperature environment. and performance stability, thereby improving the strength of the board; the bismaleimide monomer contains two highly active maleimide functional groups, which can react chemically with other resin components during the polymerization reaction, greatly increasing the cross-linking density of the resin system, and then optimizing the internal network structure of the material, so that the strength and modulus of the board are significantly improved to meet the needs of high-strength application scenarios; the acyl chloride-modified carbon nanotubes, the acyl chloride groups on their surfaces have good chemical reactivity after being modified, and can form a stable connection with the active groups in the resin in the system through covalent bonds, optimizing the interfacial bonding state between different components, so that the load can be efficiently transferred between the components, and improving the overall mechanical properties and strength from a microscopic level.
[0026] 2. Bisphenol A epoxy resin has good mechanical properties and provides basic strength support for the board. The epoxy groups in its molecules can participate in the cross-linking reaction to build a stable resin network structure. The amino groups of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane can form chemical bonds with the oxygen-containing functional groups on the surface of carbon fibers. After hydrolysis, the siloxane groups can be closely connected with the epoxy resin, and the interfacial bonding force between the carbon fibers and the resin matrix can be strengthened by bridging, so that the external force can be more efficiently transmitted from the carbon fibers to the resin matrix, and the load can be coordinated, thereby improving the overall strength. degree; the mercapto group in 3-mercaptopropyltriethoxysilane can participate in the curing reaction of epoxy resin, optimize the cross-linking network, and enhance the cohesion of the resin matrix; at the same time, the silane part improves the compatibility of epoxy resin with other components and reduces internal stress concentration; in a high temperature environment, the coupling agent-modified epoxy resin system can effectively inhibit the thermal motion of the molecular chain and hinder the thermal degradation process by virtue of its tight and stable chemical bonding and optimized cross-linking structure, thereby significantly improving the thermal stability of the material and ensuring the reliable performance of the high-strength carbon fiber plate under severe thermal conditions.
[0027] 3. The 4,4'-diaminodiphenyl ether in the composite diamine monomer has a symmetrical and regular molecular structure. Its amino group can efficiently react with 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride to build a stable initial molecular chain structure, giving the material initial strength; the phenoxy structure of 1,3-bis(4-aminophenoxy)benzene breaks the tight stacking of conventional molecular chains and gives the molecular chain flexibility. When subjected to force, the two work together, and the rigid chain segment dominated by 4,4'-diaminodiphenyl ether serves as the core bearing structure to strongly support external forces. 1,3-bis(4-aminophenoxy)benzene The flexible phenoxy group of 4-aminophenoxy)benzene acts as a buffer, flexibly adjusts the relative position between molecular chains, evenly disperses stress, reduces the risk of material fracture, and synergistically improves strength; in a high temperature environment, the rigid benzene ring of 4,4'-diaminodiphenyl ether and the rigid part of 1,3-bis(4-aminophenoxy)benzene jointly regulate the thermal motion of the molecular chain, and the flexible phenoxy group relieves the internal stress caused by thermal expansion and contraction. The strong hydrogen bonds formed within and between the two molecules further strengthen the molecular connection network and stabilize the material structure, thereby improving the thermal stability of the carbon fiber board. DETAILED DESCRIPTION
[0028] The present application discloses a high-strength carbon fiber plate and a processing technology thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw material description: The carbon fiber cloth used in this application is a bidirectional carbon fiber cloth, bisphenol A epoxy resin (CAS No.: 25085-99-8), N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (CAS No.: 1760-24-3), 3-mercaptopropyltriethoxysilane (CAS No.: 14814-09-6), 4,4'-diaminodiphenyl ether (CAS No.: 101-80-4), 1,3-bis(4-aminophenoxy)benzene (CAS No.: 2479-46-1), 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride (CAS No.: 2421-87-3), multi-walled carbon nanotube model XFM34, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., thionyl chloride (CAS No.: 7719-09-7), N-methylpyrrolidone (CAS No.: 872-50-4), triethylamine (CAS No.: 121-44-8), bismaleimide monomer is 4,4'-bismaleimidodiphenylmethane (CAS No.: 13676-54-5), curing agent is amino-terminated polyether (CAS No.: 9046-10-0), diluent is allyl glycidyl ether (CAS No.: 106-92-3), antioxidant is antioxidant 1010 (CAS No.: 6683-19-8), ultraviolet absorber is UV-327 (CAS No.: 3864-99-1).
[0029] Example 1 Preparation of coupling agent modified epoxy resin 5 kg of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3 kg of 3-mercaptopropyltriethoxysilane were mixed and dispersed in 20 L of anhydrous ethanol, and stirred at a speed of 200 rpm for 15 minutes to obtain a coupling agent solution; the coupling agent solution was added to 50 kg of bisphenol A epoxy resin within 30 minutes. After the addition was completed, the temperature was raised to 60° C. and stirred at a speed of 200 rpm for reaction for 2 hours, and the solvent was removed by rotary evaporation to obtain a coupling agent-modified epoxy resin.
[0030] Preparation of polyimide prepolymer 4,4'-diaminodiphenyl ether and 1,3-bis(4-aminophenoxy)benzene are mixed and dispersed in N,N-dimethylacetamide, and stirred at a speed of 200 rpm for 15 minutes to prepare a composite diamine monomer solution with a mass concentration of 20%; 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is added to the composite diamine monomer solution so that the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is 0.6:0.4:1, and the addition is completed within 1 hour. The reaction temperature is controlled to be 25°C, and the reaction is stirred at a speed of 300 rpm for 4 hours. The solvent is removed by rotary evaporation to obtain a polyimide prepolymer.
[0031] Preparation of acyl chloride modified carbon nanotubes 10 kg of multi-walled carbon nanotubes were dispersed in a mixed acid consisting of 30 L of sulfuric acid and 10 L of nitric acid, with the concentration of sulfuric acid being 98% and the concentration of nitric acid being 70%. The mixture was stirred at 200 rpm for 3 h in an oil bath at 60 ° C. The mixture was filtered and washed with deionized water until the filtrate was neutral. The washed carbon nanotubes were vacuum dried at 80 ° C to obtain oxidized carbon nanotubes.
[0032] 6.25 kg of oxidized carbon nanotubes and 3.75 kg of thionyl chloride were mixed and dispersed in 20 L of N-methylpyrrolidone, 0.3 kg of triethylamine was added, and the reaction was stirred at 150 rpm at 75 ° C for 12 hours under nitrogen protection. After cooling to 30 ° C, the solvent was removed by rotary evaporation, and the product was washed by filtration with anhydrous ethanol. The washed product was vacuum dried at 60 ° C to obtain acyl chloride-modified carbon nanotubes.
[0033] Preparation of slurry 30 kg of coupling agent modified epoxy resin, 20 kg of polyimide prepolymer, 15 kg of bismaleimide monomer and 3 kg of acyl chloride modified carbon nanotubes were mixed, and stirred at a speed of 300 rpm for 15 min to obtain a premix; 8 kg of curing agent was dissolved in 20 L of anhydrous ethanol to obtain a curing agent solution, and the curing agent solution was added to the premix, and stirred at a speed of 300 rpm during the addition process. The addition was completed within 30 min, 5 kg of diluent was added, and stirring was continued at a speed of 300 rpm for 30 min, 1 kg of antioxidant and 1 kg of ultraviolet absorber were added, and stirring was carried out at a speed of 500 rpm for 1 hour to obtain a slurry.
[0034] Preparation of high-strength carbon fiber plates The carbon fiber cloth is impregnated into the slurry, and a pressure of 0.3 MPa is applied during the impregnation process to obtain a prepreg; the prepreg is dried at 100°C for 1 hour to remove the solvent to obtain a preliminary cured prepreg; the preliminary cured prepreg is cut and placed in a mold for hot pressing at a temperature of 200°C, a pressure of 6 MPa, and a hot pressing time of 4 hours. After cooling to below 30°C, demolding is performed to obtain a high-strength carbon fiber board.
[0035] Example 2 Preparation of coupling agent modified epoxy resin 5 kg of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3 kg of 3-mercaptopropyltriethoxysilane were mixed and dispersed in 20 L of anhydrous ethanol, and stirred at a speed of 200 rpm for 15 minutes to obtain a coupling agent solution; the coupling agent solution was added to 50 kg of bisphenol A epoxy resin within 30 minutes. After the addition was completed, the temperature was raised to 60° C. and stirred at a speed of 200 rpm for reaction for 2 hours, and the solvent was removed by rotary evaporation to obtain a coupling agent-modified epoxy resin.
[0036] Preparation of polyimide prepolymer 4,4'-diaminodiphenyl ether and 1,3-bis(4-aminophenoxy)benzene are mixed and dispersed in N,N-dimethylacetamide, and stirred at a speed of 200 rpm for 15 minutes to prepare a composite diamine monomer solution with a mass concentration of 20%; 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is added to the composite diamine monomer solution so that the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is 0.7:0.3:1, and the addition is completed within 1 hour. The reaction temperature is controlled to 25°C, and the reaction is stirred at a speed of 300 rpm for 4 hours. The solvent is removed by rotary evaporation to obtain a polyimide prepolymer.
[0037] Preparation of acyl chloride modified carbon nanotubes 10 kg of multi-walled carbon nanotubes were dispersed in a mixed acid consisting of 30 L of sulfuric acid and 10 L of nitric acid, with the concentration of sulfuric acid being 98% and the concentration of nitric acid being 70%. The mixture was stirred at 200 rpm for 3 h in an oil bath at 60 ° C. The mixture was filtered and washed with deionized water until the filtrate was neutral. The washed carbon nanotubes were vacuum dried at 80 ° C to obtain oxidized carbon nanotubes.
[0038] 5.56 kg of oxidized carbon nanotubes and 4.44 kg of thionyl chloride were mixed and dispersed in 20 L of N-methylpyrrolidone, 0.3 kg of triethylamine was added, and the reaction was stirred at 150 rpm at 75 ° C for 12 hours under nitrogen protection. After cooling to 30 ° C, the solvent was removed by rotary evaporation, and the product was washed by suction with anhydrous ethanol. The washed product was vacuum dried at 60 ° C to obtain acyl chloride modified carbon nanotubes.
[0039] Preparation of slurry 40 kg of coupling agent modified epoxy resin, 30 kg of polyimide prepolymer, 25 kg of bismaleimide monomer and 5 kg of acyl chloride modified carbon nanotubes were mixed, and stirred at a speed of 300 rpm for 15 min to obtain a premix; 12 kg of curing agent was dissolved in 20 L of anhydrous ethanol to obtain a curing agent solution, and the curing agent solution was added to the premix, and stirred at a speed of 300 rpm during the addition process. The addition was completed within 30 min, 10 kg of diluent was added, and stirring was continued at a speed of 300 rpm for 30 min, 2 kg of antioxidant and 2 kg of ultraviolet absorber were added, and stirring was carried out at a speed of 500 rpm for 1 hour to obtain a slurry.
[0040] Preparation of high-strength carbon fiber plates The carbon fiber cloth is impregnated into the slurry, and a pressure of 0.3 MPa is applied during the impregnation process to obtain a prepreg; the prepreg is dried at 100°C for 1 hour to remove the solvent to obtain a preliminary cured prepreg; the preliminary cured prepreg is cut and placed in a mold for hot pressing at a temperature of 200°C, a pressure of 6 MPa, and a hot pressing time of 4 hours. After cooling to below 30°C, demolding is performed to obtain a high-strength carbon fiber board.
[0041] Example 3 Preparation of coupling agent modified epoxy resin 5 kg of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3 kg of 3-mercaptopropyltriethoxysilane were mixed and dispersed in 20 L of anhydrous ethanol, and stirred at a speed of 200 rpm for 15 minutes to obtain a coupling agent solution; the coupling agent solution was added to 50 kg of bisphenol A epoxy resin within 30 minutes. After the addition was completed, the temperature was raised to 60° C. and stirred at a speed of 200 rpm for reaction for 2 hours, and the solvent was removed by rotary evaporation to obtain a coupling agent-modified epoxy resin.
[0042] Preparation of polyimide prepolymer 4,4'-diaminodiphenyl ether and 1,3-bis(4-aminophenoxy)benzene are mixed and dispersed in N,N-dimethylacetamide, and stirred at a speed of 200 rpm for 15 minutes to prepare a composite diamine monomer solution with a mass concentration of 20%; 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is added to the composite diamine monomer solution so that the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is 0.65:0.35:1, and the addition is completed within 1 hour. The reaction temperature is controlled to be 25°C, and the reaction is stirred at a speed of 300 rpm for 4 hours. The solvent is removed by rotary evaporation to obtain a polyimide prepolymer.
[0043] Preparation of acyl chloride modified carbon nanotubes 10 kg of multi-walled carbon nanotubes were dispersed in a mixed acid consisting of 30 L of sulfuric acid and 10 L of nitric acid, with the concentration of sulfuric acid being 98% and the concentration of nitric acid being 70%. The mixture was stirred at 200 rpm for 3 h in an oil bath at 60 ° C. The mixture was filtered and washed with deionized water until the filtrate was neutral. The washed carbon nanotubes were vacuum dried at 80 ° C to obtain oxidized carbon nanotubes.
[0044] 5.88 kg of oxidized carbon nanotubes and 4.12 kg of thionyl chloride were mixed and dispersed in 20 L of N-methylpyrrolidone, 0.3 kg of triethylamine was added, and the reaction was stirred at 150 rpm at 75 ° C for 12 hours under nitrogen protection. After cooling to 30 ° C, the solvent was removed by rotary evaporation, and the product was washed by filtration with anhydrous ethanol. The washed product was vacuum dried at 60 ° C to obtain acyl chloride-modified carbon nanotubes.
[0045] Preparation of slurry 35 kg of coupling agent modified epoxy resin, 25 kg of polyimide prepolymer, 20 kg of bismaleimide monomer, and 4 kg of acyl chloride modified carbon nanotubes were mixed, and stirred at a speed of 300 rpm for 15 minutes to obtain a premix; 10 kg of curing agent was dissolved in 20 L of anhydrous ethanol to obtain a curing agent solution, and the curing agent solution was added to the premix, and stirred at a speed of 300 rpm during the addition process. The addition was completed within 30 minutes, 7.5 kg of diluent was added, and stirring was continued at a speed of 300 rpm for 30 minutes, 1.5 kg of antioxidant and 1.5 kg of ultraviolet absorber were added, and stirring was carried out at a speed of 500 rpm for 1 hour to obtain a slurry.
[0046] Preparation of high-strength carbon fiber plates The carbon fiber cloth is impregnated into the slurry, and a pressure of 0.3 MPa is applied during the impregnation process to obtain a prepreg; the prepreg is dried at 100°C for 1 hour to remove the solvent to obtain a preliminary cured prepreg; the preliminary cured prepreg is cut and placed in a mold for hot pressing at a temperature of 200°C, a pressure of 6 MPa, and a hot pressing time of 4 hours. After cooling to below 30°C, demolding is performed to obtain a high-strength carbon fiber board.
[0047] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane is not added when preparing the coupling agent-modified epoxy resin.
[0048] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that 3-mercaptopropyltriethoxysilane is not added when preparing the coupling agent-modified epoxy resin in Example 5.
[0049] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is 0.5:0.5:1.
[0050] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is 0.8:0.2:1.
[0051] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of oxidized carbon nanotubes used is 7.14 kg, and the amount of thionyl chloride used is 2.86 kg.
[0052] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of oxidized carbon nanotubes used is 5 kg, and the amount of thionyl chloride used is 5 kg.
[0053] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the oxidized carbon nanotubes are replaced by carbon nanotubes.
[0054] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the coupling agent-modified epoxy resin is replaced by bisphenol A epoxy resin.
[0055] Comparative Example 2 Comparative Example 2 is based on Example 3. The only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the raw materials for preparing the polyimide prepolymer are replaced with 4,4'-diaminodiphenyl ether and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride in a molar ratio of 1:1.
[0056] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that no bismaleimide monomer is added in Comparative Example 3.
[0057] Comparative Example 4 Comparative Example 4 is based on Example 3, and the only difference between Comparative Example 4 and Example 3 is that in Comparative Example 4, the acyl chloride-modified carbon nanotubes are replaced with carbon nanotubes.
[0058] Performance testing (1) GB / T1447-2005 Test method for tensile properties of fiber reinforced plastics, GB / T1449-2005 Test method for flexural properties of fiber reinforced plastics and GB / T30969-2014 Test method for short beam shear strength of polymer matrix composites were selected as the standards to test the longitudinal strength and modulus of the specimens. Five samples were prepared for each specimen, and the average value was taken after measurement. The results are recorded in Tables 1 and 2.
[0059] (2) Select GB / T2572-2005 Test method for average linear expansion coefficient of fiber reinforced plastics as the standard to test the linear expansion coefficient of the sample. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 2.
[0060] Table 1 Test results of tensile properties and bending properties of carbon fiber plates Table 2 Test results of tensile properties and bending properties of carbon fiber plates Test results Shear strength(GPa) Shear modulus(GPa) <![CDATA[Coefficient of linear expansion (10 -6 / K)]]> Example 1 122.34 30.87 1.25 Example 2 122.43 30.95 1.26 Example 3 122.46 31.11 1.23 Example 4 117.62 29.34 1.42 Example 5 116.35 28.97 1.46 Example 6 119.53 29.87 1.33 Example 7 118.69 29.51 1.36 Example 8 118.26 29.85 1.38 Example 9 116.85 28.84 1.47 Example 10 119.33 29.62 1.34 Comparative Example 1 113.84 27.58 1.52 Comparative Example 2 114.36 28.14 1.50 Comparative Example 3 98.75 25.41 2.33 Comparative Example 4 116.24 28.35 1.51 It can be seen from Table 1 and Table 2 that the tensile strength of Examples 1-3 is greater than 1238.24 MPa, the tensile modulus is greater than 89.62 GPa, the flexural strength is greater than 967.35 MPa, the flexural modulus is greater than 78.58 GPa, the shear strength is greater than 122.34 GPa, the shear modulus is greater than 30.87 GPa, and the linear expansion coefficient is less than 1.26×10 -6 / K, it can be seen that the carbon fiber plate prepared in the present application has high strength and good thermal stability.
[0061] It can be seen from Table 1 and Table 2 that the only difference between Examples 4 and 5 and Example 3 is that: in Example 4, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane is not added when preparing the coupling agent-modified epoxy resin, and in Example 5, 3-mercaptopropyltriethoxysilane is not added when preparing the coupling agent-modified epoxy resin. Compared with Example 3, the strength and thermal stability of Examples 4 and 5 are reduced; this is because the reduction of the synthetic components in the coupling agent-modified epoxy resin will affect the interfacial bonding strength and crosslinking density of the epoxy resin, thereby reducing the performance of the carbon fiber board.
[0062] It can be seen from Table 1 and Table 2 that the difference between Examples 6 and 7 and Example 3 is that the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride in Example 6 is 0.5:0.5:1, and the molar ratio of 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride in Example 7 is 0.8:0.2:1. Compared with Example 3, the strength and thermal stability of Examples 6 and 7 are reduced. This is because the ratio of the polyimide prepolymer is destroyed, and the change in the number of flexible groups will affect the stacking and performance of the molecular chain, and then affect the microstructure inside the carbon fiber board, so that the strength and thermal stability are affected.
[0063] It can be seen from Table 1 and Table 2 that the only difference between Examples 8, 9, and 10 and Example 3 is that in Example 8, the mass ratio of oxidized carbon nanotubes to thionyl chloride is 1:0.4, in Example 9, the mass ratio of oxidized carbon nanotubes to thionyl chloride is 1:1, and in Example 10, the oxidized carbon nanotubes are replaced by carbon nanotubes. Compared with Example 3, the strength and thermal stability of Examples 8, 9, and 10 are reduced; this is because the components and dosage of the acyl chloride-modified carbon nanotubes are adjusted, and the introduction of too many or too few acyl chloride groups will affect the performance of the carbon nanotubes. Too many acyl chloride groups will cause the performance of the carbon nanotubes to change and the performance to decline, while too few acyl chloride groups will result in insufficient modification effect and limited performance improvement; when the oxidized carbon nanotubes are replaced by carbon nanotubes, the active groups on the surface are reduced and the performance is reduced.
[0064] It can be seen from Table 1 and Table 2 that the only difference between Comparative Example 1 and Example 3 is that: in Comparative Example 1, the coupling agent-modified epoxy resin is replaced with a bisphenol A-type epoxy resin. Compared with Example 3, the strength and thermal stability of Comparative Example 1 are reduced; this is because the lack of modification treatment with a coupling agent reduces the crosslinking degree and interfacial bonding strength of the epoxy resin, thereby reducing the performance of the carbon fiber board.
[0065] It can be seen from Table 1 and Table 2 that the difference between Comparative Example 2 and Example 3 is that: in Comparative Example 2, the raw materials for preparing the polyimide prepolymer are replaced with 4,4'-diaminodiphenyl ether and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride in a molar ratio of 1:1. Compared with Example 3, the strength and thermal stability of Comparative Example 2 are reduced; this is because the molecular chain of the polyimide prepolymer lacks regulation due to the lack of introduction of phenoxy groups, the microstructure is affected, and the performance is reduced.
[0066] It can be seen from Table 1 and Table 2 that the difference between Comparative Example 3 and Example 3 is that no bismaleimide monomer is added in Comparative Example 3, and the strength and thermal stability of Comparative Example 3 are reduced compared with Example 3; this is because the lack of the introduction of bismaleimide monomer weakens the bonding force between the carbon fiber cloth and the resin matrix, reduces the heat resistance, and significantly reduces the strength and thermal stability.
[0067] It can be seen from Table 1 and Table 2 that the only difference between Comparative Example 4 and Example 3 is that: Comparative Example 4 replaces the acyl chloride-modified carbon nanotubes with carbon nanotubes. Compared with Example 3, the strength and thermal stability of Comparative Example 4 are reduced; this is because the carbon nanotubes lack acyl chloride modification, the dispersibility and reaction activity are reduced, the improvement effect on the system is reduced, and thus the performance of the carbon fiber board is reduced.
[0068] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high-strength carbon fiber plate, characterized in that: The raw materials include carbon fiber cloth and slurry, and the slurry includes the following components in parts by weight: 30-40 parts of coupling agent modified epoxy resin Polyimide prepolymer 20-30 parts 15-25 parts of bismaleimide monomer 3-5 parts of acyl chloride modified carbon nanotubes 8-12 parts of curing agent 5-10 parts of diluent 1-2 servings of antioxidants 1-2 parts of ultraviolet absorber.
2. A high-strength carbon fiber plate according to claim 1, characterized in that: The raw materials for preparing the coupling agent modified epoxy resin include bisphenol A type epoxy resin, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
3. A high-strength carbon fiber plate according to claim 2, characterized in that: The coupling agent modified epoxy resin is prepared by the following steps: N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane are mixed and dispersed in ethanol, and stirred to obtain a coupling agent solution; the coupling agent solution is added to bisphenol A type epoxy resin, the temperature is raised and stirred to react, and the solvent is removed by rotary evaporation to obtain a coupling agent modified epoxy resin.
4. The high-strength carbon fiber plate according to claim 1, characterized in that: The raw materials for preparing the polyimide prepolymer include a composite diamine monomer and 3,3',4,4'-dibenzophenone tetraacid dianhydride.
5. The high-strength carbon fiber plate according to claim 4, characterized in that: The complex diamine monomer includes 4,4'-diaminodiphenyl ether and 1,3-bis(4-aminophenoxy)benzene.
6. The high-strength carbon fiber plate according to claim 5, characterized in that: The molar ratio of the 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene and 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride is (0.6-0.7):(0.3-0.4):
1.
7. The high-strength carbon fiber plate according to claim 1, characterized in that: The bismaleimide monomer includes 4,4'-bismaleimidodiphenylmethane.
8. The high-strength carbon fiber plate according to claim 1, characterized in that: The raw materials for preparing the acyl chloride modified carbon nanotubes include oxidized carbon nanotubes and thionyl chloride.
9. The high-strength carbon fiber plate according to claim 8, characterized in that: The mass ratio of the oxidized carbon nanotubes to thionyl chloride is 1:(0.6-0.8).
10. A processing technology applied to the high-strength carbon fiber board according to any one of claims 1 to 9, characterized in that: The following steps are involved: The carbon fiber cloth is impregnated into the slurry, and pressure is applied during the impregnation process to obtain a prepreg; The prepreg is heated and dried to obtain a preliminary cured prepreg; the preliminary cured prepreg is cut and placed in a mold for hot pressing, and after cooling, it is demoulded to obtain a high-strength carbon fiber plate.
Citation Information
Patent Citations
Preparation technology of novel copper-clad plate
CN109747263A
High-strength carbon fiber material for wind power blade and preparation method of high-strength carbon fiber material
CN116948361A
Modified bismaleimide resin / carbon fiber prepreg as well as preparation method and application thereof
CN118562177A
Carbon fiber prepreg, preparation method thereof and application of carbon fiber prepreg in fin structural member
CN118909400A
Epoxy resin composition, prepreg, and fiber reinforced plastic material
US20190169356A1
Cited By
Polyimide-based insulating resin with high stability and high adhesive force and preparation method thereof
CN121022096A